The Mediating Effect of Eco-Innovation between Motivation and Organization Performance in Jordan Industrial Estates Company in Jordan - Alhyasat, Waleed Mohammad Kayed; Sharif, Zainon Mat; Alhyasat, Khaled Mohammad (International Journal of Engineering and Technology, 2018)
The main aim of this paper is to evaluate the effect of motivation on organization performance in Jordan Industrial Estate Company (JIEC) in Jordan, the mediating role of eco-innovation. Resource Based View theory (RBV) highlighted the role of Motivation in achieving the high organization performance. A quantitative approach and simple random sampling were used to obtain data via questionnaire from 381 employees from different level of JIEC, the response rate was 74.8%. SEM was employed to analyses the study variables. The results shows that the direct effect of motivation and eco-innovation on organization performance are significant at a p-value 0.050 and 0.000 for motivation and eco-innovation respectively and eco-innovation mediates the relationship between motivation and organization performance, with a partial mediating effect. This paper contribute to theory by filling the gap of eco-innovation literature in developing countries, validate eco-innovation as a mediator variable between motivation and organization performance. This study recommended for further studies about eco-innovation in developing countries particularly in Jordan, and repeat the same study to ensure the validate the study model.